Improvement of diabetic wound healing by topical application of Vicenin-2 hydrocolloid film on Sprague Dawley rats - Woan Sean Tan, Sean Tan; Arulselvan, Palanisamy; Ng, Shiow-Fern; Mat Taib, Che Norma; Sarian, Murni Nazira; Fakurazi, Sharida (BioMed Central, 2019)
Background: Impaired wound healing is a debilitating complication of diabetes that leads to significant morbidity, particularly foot ulcers. The risk of developing diabetic foot ulcers for diabetic patients is 15% over their lifetime and approximately 85% of limb amputations is caused by non-healing ulcers. Unhealed, gangrenous wounds destroy the structural integrity of the skin, which acts as a protective barrier that prevents the invasion of external noxious agents into the body. Vicenin-2 (VCN-2) has been reported to contain prospective anti-oxidant and anti-inflammatory properties that enhance cell proliferation and migration. Sodium Alginate (SA) is a natural polysaccharide that possesses gel forming properties and has biodegradable and biocompatible characteristics. Therefore, the objective of this study is to evaluate the effect of SA wound dressings containing VCN-2 on diabetic wounds. Methods: Wounds were inflicted in type-1 diabetic-streptozotocin (STZ) induced male Sprague Dawley rats. Subsequently, relevant groups were topically treated with the indicated concentrations (12.5, 25 and 50 μM) of VCN-2 hydrocolloid film over the study duration (14 days). The control group was treated with vehicle dressing (blank or allantoin). Wounded tissues and blood serum were collected on 0, 7 and 14 days prior to sacrifice. Appropriate wound assessments such as histological tests, nitric oxide assays, enzyme-linked immunosorbent assays (ELISA) and immunoblotting assays were conducted to confirm wound healing efficacy in the in vivo model. One-way Analysis of Variance (ANOVA) was used for statistical analysis. Results: Results showed that hydrocolloid film was recapitulated with VCN-2 enhanced diabetic wound healing in a dose-dependent manner. VCN-2 reduced pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α), mediators (iNOS and COX-2), and nitric oxide (NO) via the NF-κB pathway. Data suggests that the VCN-2 film facilitated healing in hyperglycemic conditions by releasing growth factors such as (VEGF and TGF-β) to enhance cell proliferation, migration, and wound contraction via the VEGF and TGF-β mechanism pathways. Conclusions: This study's findings suggest that VCN-2 may possess wound healing potential since topical treatment with VCN-2 hydrocolloid films effectively enhanced wound healing in hyperglycemic conditions.